Management of a Maxillary Central Incisor with Crown Fracture and Pulp Necrosis Using Porcelain-Fused-to-Metal Jacket Crown after Root Canal Treatment : Management of Traumatized Maxillary Incisor - Fitriani Fitriani; Juwita Raditya Ningsih (Universitas Syiah Kuala, 2025)
Anterior tooth trauma often causes crown fractures that can be accompanied by pulp involvement. In cases of pulp necrosis, root canal treatment is the primary option before rehabilitation with crown restoration. This case report discusses the treatment of a 23-year-old female patient who complained of a fractured front tooth after an accident. Clinical and radiographic examinations revealed pulp necrosis of the maxillary central incisor (11). Treatment consisted of root canal cleaning and shaping, irrigation, intracanal calcium hydroxide medication, and obturation using gutta-percha and endomethasone sealer. The final stage was restoration with a porcelain-fused-to-metal (PFM) jacket crown without a post, preserving the remaining tooth structure. Post-treatment evaluation showed good results, with adequate retention and stabilization, good margin adaptation, appropriate color, and no subjective patient complaints. This report emphasizes that PFM jacket crown restoration in anterior teeth after root canal treatment can provide good function and esthetics, and a good prognosis, without the need for a post when sufficient residual tissue is present.